Canada’s Unwritten Constitutional Order: Conventions and Structural Analysis - Rowe, The Honourable Malcolm; Déplanche, Nicolas (The Canadian Bar Review, 2020)
This article describes constitutional conventions, and the underlying principles of the Constitution assessed through structural analysis, as two interrelated components of Canada’s unwritten constitution. Whereas conventions and structural analysis differ in their relationship with the text of constitutional instruments, and in regard with their normative power, they perform similar functions in our constitutional order as they both seek to give effect to broad and enduring principles undergirding the organization of the state.